Parents’ Involvement in Children’s English Language Learning - Dewi, Sri Surya (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
English has become a crucial language needs to be learned by all of the students in Indonesia. Its significances for both the education and career drive English to be a subject assessed in the National Exam. From the aforementioned issue, this study attempts to investigate three points such as parents’ perceptions and parents’ involvement of their children’s English Language learning (ELL), and their perceptions related to their involvement in their children’s ELL. Since this study was conducted to portray the natural context and interpret the parents’ behavior, qualitative approach with basic qualitative is applied. Accordingly, interviews with both parents and children were also conducted to gain the data. The finding shows that 7 out of 11 parents have positive perception about their children’s ELL, whilst the rest have negative perceptions. Moreover, it was found that there are three categories of parents’ involvements, including learning at home, decision-making, and collaborating with community. From those two mentioned points concerning the parents’ perceptions and involvements, it can be seen that the parents’ involvement is strongly influenced by the perceptions which they possessed. The more positive the parents' attitude towards English, the more participation they administer to support their children’s ELL.